Assessment of the contributing risk factors in adult diabetic patients attending the diabetic clinic in Bankura Sammilani Medical College, Bankura - Padmey, Indu; De, Arindam; Gazi, Eashin; Sarkar, Aditya Prasad; Saren, Asit Baran; Mahapatra, Banamali Sinha (International Journal Of Community Medicine And Public Health, 2020)
Background: Diabetes affects all segments of the population and is one of the leading causes of premature morbidity and mortality and requires life-long healthcare services. The National Rural Health Mission launched in 2005 and the new pilot National Programme for Prevention and Control of Diabetes, Cardiovascular diseases and Stroke offer opportunities for improving care for diabetes and other non-communicable diseases through service provision at the primary and secondary levels of care. This article describes the health services related factors and ascertains the physical status of adult diabetic patients. Methods: It is an institution based, cross-sectional, descriptive study. Complete enumeration of all patients attending diabetic clinic of Bankura Sammilani Medical College and hospital, Bankura, West Bengal was done. Eligible consenting adult patients, who were diagnosed as a case of diabetes and on treatment were interviewed with review of medical record. The study was preceded after obtaining ethical clearance. Data were entered in MS Excel spread sheet. Calculation was done with the help of software SPSS 22.0 free version. Results: Only 5.3% of study subjects had drug supply from hospital fully but rest of them had to buy from the shop. 79.3% of study subjects skipped the drug when it was finished. Diabetic complication was found to be more when distance of home from hospital was more. Conclusions: Antidiabetic drug were not regularly available in hospital so all most all had to purchase drug from the shop when not available at hospital.